2022
DOI: 10.1186/s12906-022-03645-7
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent alteration in inflammatory biomarker gene expression and oxidative stress: how aerobic training and vitamin D improve T2DM

Abstract: Background Vitamin D (Vit D) supplementation and Aerobic Training (AT) exert several beneficial effects such as antioxidant and anti-inflammatory actions. The literature on the effects of AT and Vit D supplementation on the oxidative stress biomarkers and gene expression of inflammatory cytokines in patients with Type 2 Diabetes Mellitus (T2DM) is limited. The present study aimed to examine the effects of AT and Vit D supplementation on inflammation and oxidative stress signaling pathways in T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 74 publications
0
5
0
4
Order By: Relevance
“…En cuanto a la información sobre el rol de la vitamina D en pacientes con diabetes mellitus tipo 2 (Tabla 1), la mayoría de artículos se relacionaba con la diabetes mellitus tipo 2, pero también hacía más relación a los otros diferentes tipos de diabetes como la diabetes tipo 1 o sus complicaciones como neuropatía diabética, pie diabético o relacionadas al sistema cardiovascular. (11,13,14,16,17,19,23,24,25,26,27) Las características fundamentales del diseño y resultados de los estudios sobre el rol de la vitamina D en pacientes diabéticos tipo II se muestra en la Tabla 2.…”
Section: Resultados Y Discusiónunclassified
See 2 more Smart Citations
“…En cuanto a la información sobre el rol de la vitamina D en pacientes con diabetes mellitus tipo 2 (Tabla 1), la mayoría de artículos se relacionaba con la diabetes mellitus tipo 2, pero también hacía más relación a los otros diferentes tipos de diabetes como la diabetes tipo 1 o sus complicaciones como neuropatía diabética, pie diabético o relacionadas al sistema cardiovascular. (11,13,14,16,17,19,23,24,25,26,27) Las características fundamentales del diseño y resultados de los estudios sobre el rol de la vitamina D en pacientes diabéticos tipo II se muestra en la Tabla 2.…”
Section: Resultados Y Discusiónunclassified
“…HOMA IR -0,81 -0,06 HOMA-B: 0,01 5 Li et al (35) 2018 Hoseini et al (17) , observaron que la actividad física, es un indicador para reducir biomarcadores inflamatorios y proteínas, pero que pueden ser reforzadas para algún proceso inflamatorio a largo plazo. Además, concluyeron que al realizar ejercicios aeróbicos y mantener una suplementación de vitamina D, la relación cintura-cadera (WHR), el índice de masa corporal (IMC), el peso corporal (BW) y el porcentaje de grasa corporal (BFP), disminuyeron sus valores, pero si solo se hace administración del placebo, no hay ningún cambio.…”
Section: Metaanálisis 29 Estudios No Menciona Hallazgosunclassified
See 1 more Smart Citation
“…It has also been shown that intensified activity-interval + strength training is required to reduce insulin intake in patients with T1DM [ 45 ]. A study by Hoseini et al [ 46 ] examined the effects of aerobic training on markers of oxidative stress and inflammation in patients with t2 diabetes. They found that an eight week intervention in the form of AT activity positively influenced glycemic control, most likely through a mechanism of increased antioxidant defense and decreased inflammatory markers (IL-1β, hs-CRP, TNF-α, interferon-γ (IFN-γ)), and increased the production of anti-inflammatory cytokines (increase in IL-4).…”
Section: Effects Of Physical Activity On Glycemic Control Oxidative S...mentioning
confidence: 99%
“…They found that an eight week intervention in the form of AT activity positively influenced glycemic control, most likely through a mechanism of increased antioxidant defense and decreased inflammatory markers (IL-1β, hs-CRP, TNF-α, interferon-γ (IFN-γ)), and increased the production of anti-inflammatory cytokines (increase in IL-4). Due to the small number of participants, conclusions should be made cautiously; however, it seems that physical activity, particularly when combined with vitamin D supplementation, is able to reduce biomarkers of oxidative stress and inflammation in patients with T2DM [ 46 ].…”
Section: Effects Of Physical Activity On Glycemic Control Oxidative S...mentioning
confidence: 99%